(untitled) (BrewingScience, 2000)
The Fourth Meeting of the International Subcommittee for Isomerised Hop α-Acids Standards was held in Keystone, Colorado, USA, on the 12th September 1999. Six full members (out of a possible twelve) were in attendance, plus one proxy member and two guests. Regrettably, on this occasion only three of the subcommittee’s four parent organisations (ASBC, EBC, IOB and BCOJ) were represented, neither of the two committee members appointed by the Institute of Brewing having been able to make the trip. Following acceptance of the Secretary’s Report of the Third (Cannes) Meeting, the Chairman (Richard Wilson, S. S. Steiner, Inc.) promptly turned the meeting’s attention to the continuing study of the purity and stability of small-scale preparations of the proposed new standards for the HPLC analysis of isomerised and reduced isomerised α-acids.